Psychometric validation of a brief self-report measure of misophonia symptoms and functional impairment: The duke-vanderbilt misophonia screening questionnaire - Williams, Zachary J.; Cascio, Carissa J.; Woynaroski, Tiffany G. (Frontiers in Psychology, 2022)
Misophonia is a newly-described disorder of sound tolerance characterized by strong negative emotional reactions to specific "trigger" sounds, resulting in significant distress, pathological avoidance, and impairment in daily life. Research on misophonia is still in its infancy, and most existing psychometric tools for assessing misophonia symptoms have not been extensively validated. The purpose of the current study was to introduce and psychometrically validate the Duke-Vanderbilt Misophonia Screening Questionnaire (DVMSQ), a novel self-report measure of misophonia symptoms that can be used to determine misophonia "caseness" in clinical and research settings. Employing large online samples of general population adults (n = 1403) and adults on the autism spectrum (n = 936), we rigorously evaluated the internal structure, reliability, validity, and measurement invariance of the DVMSQ. Results indicated that 17 of the 20 original DVMSQ items fit well to a bifactor structure with one "general misophonia" factor and four specific factors (anger/aggression, distress/avoidance, impairment, and global impact). DVMSQ total and subscale scores were highly reliable in both general population and autistic adult samples, and the measure was found to be approximately invariant across age, sex, education level, and autism status. DVMSQ total scores also correlated strongly with another measure of misophonia symptoms (Duke Misophonia Questionnaire–Symptom Scale), with correlations between these two measures being significantly stronger than correlations between the DVMSQ and scales measuring other types of sound intolerance (Inventory of Hyperacusis Symptoms [General Loudness subscale] and DSM-5 Severity Measure for Specific Phobia [modified for phonophobia]). Additionally, DVMSQ items were used to operationalize diagnostic criteria for misophonia derived from the Revised Amsterdam Criteria, which were further updated to reflect a recent consensus definition of misophonia (published after the development of the DVMSQ). Using the new DVMSQ algorithm, 7.3% of general population adults and 35.5% of autistic adults met criteria for clinically significant misophonia. Although additional work is needed to further investigate the psychometric properties of the DVMSQ and validate its theory-based screening algorithm using best-estimate clinical diagnoses, this novel measure represents a potentially useful tool to screen for misophonia and quantify symptom severity and impairment in both autistic adults and the general population.